2017
DOI: 10.1111/bju.13828
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of kidney stones in China: an ultrasonography based cross‐sectional study

Abstract: A nationwide cross-sectional survey was conducted among individuals aged ≥18 years across China, from May 2013 to July 2014. Participants underwent urinary tract ultrasonographic examinations, completed pre-designed and standardised questionnaires, and provided blood and urine samples for analysis. Kidney stones were defined as particles of ≥4 mm. Prevalence was defined as the proportion of participants with kidney stones and binary logistic regression was used to estimate the associated factors. ResultsA tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
209
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 347 publications
(238 citation statements)
references
References 25 publications
11
209
2
Order By: Relevance
“…In China, national epidemiological studies of kidney stones are extremely limited. Lately, a cross‐sectional study of general population based on urinary tract ultrasonography determination shows that the prevalence of kidney stones in China was 5.8% (6.5% in men and 5.1% in women), and the ‘self‐report’ prevalence was 11.7% . Our study describes an increasing trend of ON largely due to kidney stones, with a substantial geographic variation (high percentage in rural residents, south and southwest areas).…”
Section: Discussionmentioning
confidence: 63%
“…In China, national epidemiological studies of kidney stones are extremely limited. Lately, a cross‐sectional study of general population based on urinary tract ultrasonography determination shows that the prevalence of kidney stones in China was 5.8% (6.5% in men and 5.1% in women), and the ‘self‐report’ prevalence was 11.7% . Our study describes an increasing trend of ON largely due to kidney stones, with a substantial geographic variation (high percentage in rural residents, south and southwest areas).…”
Section: Discussionmentioning
confidence: 63%
“…A study of healthy volunteers showed green tea consumption was associated with increased urinary oxalate . However, several epidemiological studies have suggested that tea intake is associated with lower stone risk . An analysis of three prospective cohort studies in the USA showed a 11% decreased risk of incident stones among those who drank 8 oz tea daily compared with less than once a week .…”
Section: Discussionmentioning
confidence: 99%
“…However, intakes of tea among participants were generally low overall (median 2–4 servings/month), and the type of tea consumed was unknown. A study of prevalent stones in China showed that tea consumption was associated with a 23% decreased risk, although the amount, duration and type of tea consumed were not specified …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nephrolithiasis is a worldwide health problem that affects almost all populations. Recent studies have shown that the prevalence of nephrolithiasis in Chinese adults is 6.5%, while the prevalence in Guangxi province in southern China is 7.82%‐12.03% . Nephrolithiasis is affected by multiple risk factors, including environment, lifestyle, hormones, anatomical factors, and genetic factors.…”
Section: Introductionmentioning
confidence: 99%